UPAYA PENINGKATAN KAPASITAS USAHA MASYARAKAT DESA EMBUNG RAJA MELALUI PELATIHAN PEMBUATAN BAKSO IKAN - Rozi, Fahrur; Lumbessy, Salnida Yuniarti; Scabra, Andre Rachmat; Yasa, Kadek Nuarta; Hafizi, Auliyan; Putri, Aulia; Larasati, Afina Praba; Tulhosiyah, Ayijah; Faujiah, Faujiah; Melina, Jennie; Oktavia, Lenny; Alfatih, Muhamad; Syaharani, Salma Akmaliah (Jurnal Wicara, 2023)
Embung Raja Village is one of the villages in the Terara sub-district, East Lombok. Based on the geographical location of this village, this village has abundant natural resource potential, including in the agricultural and fisheries sectors. Based on the results of a survey conducted, the challenge that is still felt by the local community is that the existing natural resources have not been utilized. The potential is in the field of fisheries, in this community service we initiated training on making fish balls in partnership with PKK women with the hope that it can be developed as a form of business for the Embung Raja village community. The series of training activities started with introducing the virtues of tilapia meat and continued with making meatballs and the packaging process using a vacuum seal. The market segmentation that is our target consumer is children and adults.